A novel Granzymes and miRNA nanocapsules co-delivery system for tumor suppression. (1st November 2022) - Shi, Zhendong; Zhao, Ming; Lin, Tianyu; Chen, Jiajia; Qian, Xiaomin
Abstract: Granzymes-based immunotherapy for the treatment of solid tumors has gained great success and played more and more important effect in clinical studies. However, the antitumor effect of Granzymes still requires improvements owing to the cell evasion and metastasis of cancer. To overcome these limitations, synergistic combinatorial anti-tumor effect of Granzyme B (GrB) and miR-21 inhibitor (miR-21i) for breast cancer therapy through a new co-delivery system was investigated in present study. GrB was covalently bonded with miR-21i by disulfide bond and encapsulated in a nanocapsule formed by in situ polymerization of N -(3-aminopropyl) methacrylamide (APM), ethylene glycol dimethacrylate (EGDMA) and 2-Methacryloyloxyethyl phosphorylcholine (MPC). The nanocapsules possessed spherical and uniform diameter size as well as pH responsiveness in various environments. MTT and flow cytometry analysis showed that a synergistic anti-proliferation and promoting apoptosis effect was achieved when the nanocapsules were added into breast cancer cell lines. More importantly, the cell evasion ability was markedly inhibited using the nanocapusles detected through transwell invasion assay. Also the in vivo anti-tumor therapeutic efficacy of GrB-miR-21i nanocapusles was evaluated in a mouse tumor model. In conclusion, the nanocapsules for simultaneously delivery of GrB and miR-21i produce a synergistic effect in human breast cancer therapy.